Reviews of new publications - Holmes, Derek A (KUKILA, 2000)
Wells, D.R 1998. The Birds of the Thai-Malay Peninsula Volume One: NonPasserines. London: Academic Press Balen, S. van. 1999. Birds on fragmented islands: persistence in the forests of Java and Bali. Doctoral thesis del Hoyo, J., A. Elliott & J. Sargatal. Eds. 1999. Handbook of the Birds of the World Vol. 5. Barn-owls to Hummingbirds. Lynx Edicions